SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU BERBASIS WEB PADA BALAI LATIHAN KERJA (BLK) KOTA CILEGON - Sulistiyono Sulistiyono; Agus Irawan; Syaiful Rizal (Program Studi Sistem Informasi, Universitas Banten Jaya, 2020)
The government through the Manpower Office has built a Job Training Center which aims to provide skills and expertise to training participants in order to improve the quality of prospective workforce. The service for admitting new students at the Cilegon City Work Training Center which is implemented has not been effective because it still uses the manual system, where participants come to the office to take the registration form. This study aims to create a web-based information system for new student admissions at the Cilegon City Work Training Center. Making this new web-based student admission information system uses the waterfall method which includes software requirements analysis, design, system coding, system testing, system support and maintenance. The web-based admission system at the Cilegon City Work Training Center can make it easier for prospective new students to register by saving time and costs compared to coming in person. With this new student admission information system, it is hoped that it can facilitate the processing of new students at the Cilegon City Work Training Center.